THE IMPORTANCE OF CULTURE IN URBAN PLANNING: A BRIEF CASE STUDY OF URBAN PLANNING IN YOGYAKARTA AND KYOTO - Kriswandwitanaya, Muhammad Farhan; Nurussobah, Ahmad Fatih (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2024)
Urban planning is a multifaceted discipline that integrates infrastructure, economy, and environment to develop sustainable cities. However, a critical yet often overlooked component is culture. Incorporating historical, social, and artistic aspects of a community into urban development not only preserves the unique identity of a city but also enhances residents' quality of life. This article explores the importance of culture in urban planning through a brief case study of Yogyakarta in Indonesia and Kyoto in Japan. These cities exemplify how cultural elements can be seamlessly integrated into urban development plans. The study utilizes a qualitative method, drawing data from literature, laws, and prior research. It analyzes the outcomes of cultural integration in urban planning in Yogyakarta and Kyoto and offers recommendations for other cities. The findings suggest that comprehensive legal frameworks, community involvement, and balanced development strategies are crucial for successful cultural preservation in urban planning. Recommendations include promoting multidisciplinary approaches, fostering public awareness, and developing tourism strategies that respect cultural heritage. By adopting these strategies, cities can create vibrant, sustainable urban environments that honor their unique cultural heritage while embracing the future.